THE EFFECT OF INFLUENCER MARKETING AND PRICE PERCEPTION ON PURCHASE DECISIONS FOR GLAD2GLOW SKINCARE PRODUCTS IN BEKASI CITY - Intan Permata Desi; Warsono; Dian Berliansyah Putra; Natal Indra (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
Influencer marketing and price perception are two important factors that influence consumer behavior, especially in the currently rapidly growing skincare industry. This study aims to analyze the influence of influencer marketing and price perception on purchasing decisions for Glad2Glow skincare products in Bekasi City. This study uses a quantitative descriptive method with a population of Glad2Glow product consumers. The research sample consisted of 96 respondents determined using the Lemeshow formula, with data collection techniques through questionnaires. The collected data were processed using the SPSS application version 24 through validity tests, reliability tests, classical assumptions, multiple linear regression, and hypothesis testing. The results indicate that influencer marketing has a positive and significant effect on purchasing decisions, with a significance value of 0.000 < 0.05 and a t-count of 4.238 > t-table 1.616. Similarly, price perception also exerts a positive and significant influence on purchasing decisions, with a significance value of 0.000 < 0.05 and a t-count of 13.048 > t-table 1.616. Furthermore, influencer marketing and price perception simultaneously have a significant effect on purchasing decisions, as evidenced by a significance value of 0.000 < 0.05 and an F-count of 391.777 > F-table 3.09. These findings suggest that effective marketing strategies through influencers combined with appropriate pricing can enhance consumer interest and strengthen purchasing decisions, thereby contributing to the competitiveness of local skincare brands.